PENGELOLAAN ZAKAT DI NEGARA SUDAN (UIN Sunan Kudus, 2017)
Sudan is one of the countries that use Islamic sharia in its government, so zakat as one of the pillars of Islam gets special attention from the Sudanese government. This article examines the management of zakat in Sudan based on established regulations. The results show that zakat is an obligation that must be paid by the people of Sudan and will be given sanctions for people who are reluctant to pay. Zakat management in Sudan is based on the Zakat Act of 2001. The implementation of zakat management in Sudan has the following characteristics: first, zakat is handled directly by the government. Second, the Zakat Board as a manager is independent. Third, Sudan implements the Federal system. And fourth, Sudan has a broad fiqh view of the object of zakat.